Longest-edge n-section algorithms: Properties and open problems - Korotov, Sergey; Plaza, Ángel; Suárez, José P. (Journal of computational and applied mathematics, 2016)
In this paper we survey all known (including own recent results) properties of the longest-edge n-section algorithms. These algorithms (in classical and recently designed conforming form) are nowadays used in many applications, including finite element simulations, computer graphics, etc. as a reliable tool for controllable mesh generation. In addition, we present a list of open problems arising in and around this topic.